HUBUNGAN PENGGUNAAN ALAT PELINDUNG TELINGA DAN MASA KERJA DENGAN GANGGUAN PENDENGARAN PEKERJA PENGGILINGAN KOPI DESA KANDANG KECAMATAN SEBERANG MUSI KABUPATEN KEPAHIANG - Ayu, Ajeng; Mualim, Mualim; Widada, Agus (LPPM STIKES BHAKTI HUSADA BENGKULU, 2024)
ABSTRAK Latar Belakang: Kebisingaln merupalkaln bunyi yalng tidalk diinginkaln dalri sualtu usalhal altalu kegialtaln dallalm tingkalt daln walktu tertentu yalng dalpalt menimbulkaln galnggualn kesehaltaln malnusial daln kenyalmalnaln lingkungaln.Tujualn Penelitialn untuk mengetalhui hubungaln penggunalaln allalt pelindung telingal daln malsal kerjal dengaln galnggualn pendengalraln paldal pekerjal penggilingaln kopi di Desal Kalndalng Kecalmaltaln Seberalng Musi Kalbupalten Kepalhialng.Metode : Metode penelitialnbersifalt dekriptif alnallitik dengaln pendekaltaln cross sectional, jumlalh salmpel sebalnyalk 60 responden, dan analisis data mengunakan Chi-Squqre.Hasil:Halsil penelitialn berdalsalrkaln penelitialn menunjukaln pengukuraln kebisingaln di penggilingaln kopi di Desal Kalndalng Kecalmaltaln Seberalng Musi Kalbupalten Kepalhialng didalpaltkaln 88,4 dBA yalng telalh melebihi Nilali Ambalng Batals, adalnyal hubungaln alntalral penggunal alat Lpelindung telinga dengaln galnggualn pendengalraln paldal pekerjal penggilingaln kopi (p=0,000<0,05) daln aldalnyal hubungaln alntalra malsal kerjal dengaln galnggualn pendengalraln paldal pekerjal penggilingaln kopi (p=0,010<0,05). Kesimpulan : Penelitialn ini dalpalt memberikaln malsukaln untuk peneliti lebih lalnjut dallalm mengembalngkaln ilmu yalng berhubungaln dengaln keselalmaltaln daln kesehaltaln kerja... Kata Kunci : Pengunalaln APT, Malsal Kerjal, Galnggualn Pendengalraln ABSTRACT Background : Noise is an unwanted sound from an event or activity at a certain level and time that can cause disturbances to human health and the surrounding environment. Research Proposal to investigate the relationship between the use of ear protection and the hearing ability of coffee grinding workers in Kandang Village, Subdistrict of Seberang Musi, Musi Rawas Regency. Method : The research method used is a descriptive analytical method with a cross-sectional approach, involving a total sample of 60 respondents, and data analysis using Chi-Square. Results : The results of the research indicate that the noise level measured in the coffee grinding facility in Kalindang Village, Subdistrict of Seberang Musi, Regency of Kepahiang reached 88.4 dBA, which exceeds the Ambient Noise Standard. Additionally, there is a significant relationship between the use of hearing protection devices and the hearing ability of workers in the coffee grinding facility (p=0.000<0.05), as well as a significant relationship between work experience and the hearing ability of workers in the coffee grinding facility (p=0.010<0.05). Conclusion : This research provides insights for future researchers in developing knowledge related to health and workplace safety. Keywords : Use of APT, Occupational Health, Hearing DisordersABSTRAK Latar Belakang: Kebisingaln merupalkaln bunyi yalng tidalk diinginkaln dalri sualtu usalhal altalu kegialtaln dallalm tingkalt daln walktu tertentu yalng dalpalt menimbulkaln galnggualn kesehaltaln malnusial daln kenyalmalnaln lingkungaln.Tujualn Penelitialn untuk mengetalhui hubungaln penggunalaln allalt pelindung telingal daln malsal kerjal dengaln galnggualn pendengalraln paldal pekerjal penggilingaln kopi di Desal Kalndalng Kecalmaltaln Seberalng Musi Kalbupalten Kepalhialng.Metode : Metode penelitialnbersifalt dekriptif alnallitik dengaln pendekaltaln cross sectional, jumlalh salmpel sebalnyalk 60 responden, dan analisis data mengunakan Chi-Squqre.Hasil:Halsil penelitialn berdalsalrkaln penelitialn menunjukaln pengukuraln kebisingaln di penggilingaln kopi di Desal Kalndalng Kecalmaltaln Seberalng Musi Kalbupalten Kepalhialng didalpaltkaln 88,4 dBA yalng telalh melebihi Nilali Ambalng Batals, adalnyal hubungaln alntalral penggunal alat Lpelindung telinga dengaln galnggualn pendengalraln paldal pekerjal penggilingaln kopi (p=0,000<0,05) daln aldalnyal hubungaln alntalra malsal kerjal dengaln galnggualn pendengalraln paldal pekerjal penggilingaln kopi (p=0,010<0,05). Kesimpulan : Penelitialn ini dalpalt memberikaln malsukaln untuk peneliti lebih lalnjut dallalm mengembalngkaln ilmu yalng berhubungaln dengaln keselalmaltaln daln kesehaltaln kerja... Kata Kunci : Pengunalaln APT, Malsal Kerjal, Galnggualn Pendengalraln ABSTRACT Background : Noise is an unwanted sound from an event or activity at a certain level and time that can cause disturbances to human health and the surrounding environment. Research Proposal to investigate the relationship between the use of ear protection and the hearing ability of coffee grinding workers in Kandang Village, Subdistrict of Seberang Musi, Musi Rawas Regency. Method : The research method used is a descriptive analytical method with a cross-sectional approach, involving a total sample of 60 respondents, and data analysis using Chi-Square. Results : The results of the research indicate that the noise level measured in the coffee grinding facility in Kalindang Village, Subdistrict of Seberang Musi, Regency of Kepahiang reached 88.4 dBA, which exceeds the Ambient Noise Standard. Additionally, there is a significant relationship between the use of hearing protection devices and the hearing ability of workers in the coffee grinding facility (p=0.000<0.05), as well as a significant relationship between work experience and the hearing ability of workers in the coffee grinding facility (p=0.010<0.05). Conclusion : This research provides insights for future researchers in developing knowledge related to health and workplace safety. Keywords : Use of APT, Occupational Health, Hearing Disorders